STUDI PERHITUNGAN VOLUME SISA ERUPSI MERAPI DENGAN DATA DEM FOTO UDARA DAN LIDAR DI SUNGAI GENDOL MERAPI - , JUANG PUTRA W ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The use of aerial photographs and DEM DEM LIDAR can help to provide spatial and attribute data to be used in the process of post-disaster management. In this project the DEM data record aerial photo models riverbed prior to the eruption and LIDAR DEM data record basic model of the river after the eruption. Two models of the data can then be calculated volume eruption of material that are then used as data in case of prevention and anticipation of rains and floods in the Gendol river. This study was preceded by the acquisition of DEM data of gendol river stream in 2 epok, epok 1989 as the first DEM data as a result of aerial photographs recording and DEM data of LIDAR in 2012. Both of these data has a different height reference system. It is known after seen the difference in the z values for each position of X and Y are the same. The average of this differences is 10,78 m with a standard deviation is 1,043 m. This height difference value is then a use for transformation for aerial photography DEM data. After the transformation process volume calculation can be done that used 2 DEM data transformations that have done this and then do a comparison. From the data result from a comparison of DEM from aerial photography and LIDAR can be calculated volume of sediment and soil material lost due to eruption of Mount Merapi. Cut value when the volume 141.517,1 fill volume is about 42.761,055 . Volume cut value is the value of the loss of soil and fill material volume is considered the value of the waste material.